Factors affecting yield of Tuber melanosporum in a Quercus ilex plantation in southern France - Shaw, P.J.a.; Lankey, K; Jourdan, A (Mycological Research, 1996)
Yields of Tuber nielanosporurn fruit bodies from a commercial truffle plantation are examined in relation to time, soil conditions and basal diameter of host tree. Fruiting started 10 yr after planting, and the number of trees producing truffles increased steadily for the following 8 yr. The best predictor of truffle production was tree basal diameter.
Keywords: host tree (PG); soil conditions; Tuber melanosporum; yield